Creative solutions for plastic waste reduction and economic empowerment in Mukim Langsa Baroh - Syahputra, Rinaldi; Ridha, Ahmad; Lisa, Nova Purnama; Ismanidar, Nur; Andiny, Puti; Setianingsih, Dias (Universitas Muhammadiyah Magelang, 2025)
Plastic waste has become an increasingly alarming environmental pollution problem. The high consumption of single-use plastics by the community significantly contributes to long-term environmental issues. This activity aimed to enhance the awareness, skills, and creativity of the community in Mukim Langsa Baroh in processing plastic waste into handicraft products with economic value. The training was conducted through lecture and direct practice methods. This activity successfully established a community group active in plastic waste processing, and participants were able to apply the skills taught in practice. The evaluation results demonstrated an increased public awareness regarding the environmental impact of plastic waste.